2020
DOI: 10.1093/ckj/sfaa058
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of dialysate bicarbonate in patients treated with online haemodiafiltration

Abstract: Background Metabolic acidosis is a common problem in haemodialysis patients, but acidosis overcorrection has been associated with higher mortality. There is no clear definition of the optimal serum bicarbonate target or dialysate bicarbonate. This study analysed the impact of reducing dialysate bicarbonate from 35 to 32 mEq/L on plasma bicarbonate levels in a cohort of patients treated with online haemodiafiltration (OL-HDF). Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 31 publications
1
16
0
2
Order By: Relevance
“…Our results were consistent with those of numerous studies demonstrating biological disorders in the blood induced by continuous decrease in renal clearance or GFR [6][7][8][9][10][11][12]. Despite the effectiveness of dialysis in filtering and purifying the blood, we found that some analytes remained at very high levels and an interpretation of the result using the existing RIs was meaningless.…”
Section: Discussionsupporting
confidence: 89%
“…Our results were consistent with those of numerous studies demonstrating biological disorders in the blood induced by continuous decrease in renal clearance or GFR [6][7][8][9][10][11][12]. Despite the effectiveness of dialysis in filtering and purifying the blood, we found that some analytes remained at very high levels and an interpretation of the result using the existing RIs was meaningless.…”
Section: Discussionsupporting
confidence: 89%
“…In a recent study assessing sodium mass balance in HD and online post‐dilution HDF, it has been shown that sodium mass removed was nearly identical, provided dialysate sodium prescription was lower than the predialysis plasma sodium concentration 42 . Usually, no specific adaptation is required for most electrolytes when compared with stable patients on maintenance high‐flux HD 43 . However, in particular cases, dialysate electrolytes prescription must be probed to patient results: particularly with more frequent or longer HDF treatment schedules and when larger convective volumes are delivered as with pre‐dilution HDF, especially when treating vulnerable populations (elderly and children), and specific conditions (parathyroid disorders, calcimimetics, and alkalotic patients).…”
Section: Hdf Prescription: Factors To Be Consideredmentioning
confidence: 99%
“…The levels of electrolytes in the dialysis fluid used for high‐volume HDF might need to be adjusted from those used in conventional hemodialysis to avoid electrolyte imbalances. For example, it may be necessary to reduce the bicarbonate concentration in the dialysis fluid to avoid over‐correction of the metabolic acidosis seen in hemodialysis patients 7 . It might also be necessary to adjust the dialysis fluid sodium concentration.…”
Section: Hdf Machinesmentioning
confidence: 99%
“…For example, it may be necessary to reduce the bicarbonate concentration in the dialysis fluid to avoid over-correction of the metabolic acidosis seen in hemodialysis patients. 7 It might also be necessary to adjust the dialysis fluid sodium concentration. The Gibbs-Donnan effect causes ultrafiltrate to have a lower sodium concentration than the plasma water from which it is derived, leading to an increase in plasma water sodium concentration along the length of the dialyzer.…”
Section: Hdf Machinesmentioning
confidence: 99%